2017
DOI: 10.1063/1.4994479
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical investigations of nanotechnological insulation materials

Abstract: Abstract. Nowadays, to sufficiently reduce the heat loss through the wall structures with the so-called traditional insulations (polystyrene and fibrous slabs), huge thicknesses (20 -25 cm) must be applied. In some cases there is no place for their applications e.g.: historical or heritage builfings, since the use of nano-insulation materials (aerogel, vacuum ceramic paints) takes place. They are said to be much more efficient insulations than the above mentioned ones, since they should be used in thinner form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In this way, after applying the linear and point heat transfer coefficients, the imposed R' values, respectively U' values, are met. A significant increase in the unidirectional thermal resistance value can be reached by thicker thermal insulation or by using super insulating materials, i.e., vacuum insulation panels and aerogel insulation [45][46][47], preponderantly recommended for LSF buildings.…”
Section: Modelled Casesmentioning
confidence: 99%
“…In this way, after applying the linear and point heat transfer coefficients, the imposed R' values, respectively U' values, are met. A significant increase in the unidirectional thermal resistance value can be reached by thicker thermal insulation or by using super insulating materials, i.e., vacuum insulation panels and aerogel insulation [45][46][47], preponderantly recommended for LSF buildings.…”
Section: Modelled Casesmentioning
confidence: 99%
“…It has also been found that thermal insulation capacity of nano-ceramic thermocoatings is affected by its thermal inertia (thermal lag). During the review of heat transfer processes, a further discovery has been made that the physical equations used for atomic diffusion can be applied to heat diffusion (Lakatos, 2017).…”
Section: Literature Summarymentioning
confidence: 99%
“…Due to the strict sustainability standards, the building industry has worked on new concepts for reducing the consumption of petrochemicals and carbon emission over the last decades . In addition to the application of wood, palm, wool, and cellulose fibers as a natural source in the building insulation, new systems with optimized energy consumption have been developed . Vacuum insulation panels (VIPs) and aerogels have been proven to be among the best thermal insulation solutions due to their extremely low thermal conductivity .…”
Section: Introductionmentioning
confidence: 99%
“…cellulose fibers as a natural source in the building insulation, new systems with optimized energy consumption have been developed. [5][6][7][8] Vacuum insulation panels (VIPs) and aerogels have been proven to be among the best thermal insulation solutions due to their extremely low thermal conductivity. 9,10 However, both materials are very costly and have some restrictions in building insulation applications.…”
mentioning
confidence: 99%